Minimax isomorphism algorithm and primitive posets - Bondarenko, V.M. (Algebra and Discrete Mathematics, 2011)
The notion of minimax equivalence of posets, and a close notion of minimax isomorphism, introduced by the author are widely used in the study of quadratic Tits forms (in particular, for the description of P-critical and P-supercritical posets). In this paper, for an important special case, we modify an algorithm of classifying all posets minimax isomorphic to a given one (described earlier by the author together with M.V.Stepochkina) by introducing the concept of weak isomorphism.